2018
DOI: 10.11606/s1518-8787.2018052000497
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with frailty in older adults

Abstract: OBJECTIVE To determine the demographic and health factors related to the frailty syndrome in older adults.METHODS This is a longitudinal quantitative study carried out with 262 older adults aged 65 years and older, of both sexes, living at home. Data collection was carried out in Period 1 between October 2007 and February 2008, and in Period 2 between July and December 2013. For data collection, we used the sociodemographic profile instrument, the Edmonton Frail Scale, the Mini-Mental State Examination, the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
1
33

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 31 publications
9
64
1
33
Order By: Relevance
“…2 Its association with poor outcomes has been demonstrated in multiple settings, from the community dwelling population to the surgical population. [3][4][5][6][7][8][9][10] This relationship appears particularly relevant in patients requiring emergent procedures. 11,12 In a recent systematic review of the spine surgery literature, frailty has been demonstrated to affect post-operative outcomes such as adverse events (AEs), mortality, and length of stay (LOS).…”
Section: Introductionmentioning
confidence: 99%
“…2 Its association with poor outcomes has been demonstrated in multiple settings, from the community dwelling population to the surgical population. [3][4][5][6][7][8][9][10] This relationship appears particularly relevant in patients requiring emergent procedures. 11,12 In a recent systematic review of the spine surgery literature, frailty has been demonstrated to affect post-operative outcomes such as adverse events (AEs), mortality, and length of stay (LOS).…”
Section: Introductionmentioning
confidence: 99%
“…This was expected as the FP is a syndrome related to the aging process 4 . Thus, the older the volunteer, the greater their likelihood of being frail 36 . On the other hand, the occlusal status, early tooth loss, presence of local and systemic pathologies or even the reduction of salivary flow rate, which are considered to play a major role in MP and MBF 21 , did not differ between groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly prevalent and needs to be better evaluated through studies with high levels of scientific evidence 1 . It should be considered that elderly patients usually suffer reduced functional capacity [30][31][32][33] , which, added to the fatigue caused by the disease 34 , may result in greater impairment of activities of daily living and interference in QoL [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%